A Notion-Based Visual Marine Engineering Dictionary for Maritime English Learning - Dhesi Wulan Sari; Deri Herdawan; Marselia Marselia; Fitri Suprapti; Alimatussa'diyah (CV. Global Cendekia Inti, 2026)
Effective communication is fundamental to ensuring safety and operational efficiency in maritime environments. However, maritime cadets frequently encounter difficulties in mastering the technical Maritime English vocabulary required for engine room operations. This study aimed to develop a Notion-based visual marine engineering dictionary integrating images of engine room components, audio pronunciations, and contextual phrases aligned with Standard Marine Communication Phrases (SMCP) to support Maritime English learning. The research adopted a Research and Development (R&D) approach using the ADDIE instructional design model, consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. The developed product was implemented with 38 marine engineering cadets at Politeknik Maritim Negeri Indonesia. Feasibility evaluation results showed mean scores ranging from 4.00 to 4.50, which were categorized as Good to Very Good. In addition, 85.0% of participants reported that the visual dictionary helped improve their understanding of marine engineering terminology. These findings indicate that the Notion-based visual dictionary is a feasible learning medium with positive potential to support cadets’ acquisition of technical Maritime English vocabulary in maritime vocational education. Nevertheless, the study was limited to a relatively small sample from a single maritime institution, indicating the need for broader implementation and further evaluation studies.